A review on the antimicrobial properties of bacterial metabolites from Serratia spp. as dye material on textile - Wan Jaafar, Wan Nor Raihan; Mohd Hisham, Adibah (Universiti Teknologi MARA (UiTM), 2024)
Synthetic dyes have long dominated industries for their cost-effectiveness, yet their environmental and health impacts are concerning. In response, natural dyes, particularly those from microbial sources are gaining attention for their ecofriendly and biodegradable properties, including unique bioactive features like antimicrobial activity. Therefore, microbial dyes such as prodigiosin from Serratia spp. is one of the alternatives to replace synthetic dyes. Despite its potential, the small extraction yield of prodigiosin limits its application in the textile industry. Moreover, Serratia spp. are found in diverse environments, yet the antimicrobial properties of prodigiosin for textile dyeing are less reported. Thus, the antimicrobial properties during human contact with various textiles are required to be reviewed. This review explores Serratia spp. as a promising microbial source for textile dyeing applications specifically focusing on producing prodigiosin pigment in mass production and its antimicrobial properties. Key questions revolve around Serratia’s ability to produce natural pigment, its benefits on textiles, and its antimicrobial properties. Recent studies indicate that optimizing bioprocess conditions and using effective substrates can significantly increase prodigiosin yields. High yields were achieved using improved bioprocess conditions in bioreactors, the one-factor-at-a-time (OFAT) approach, and the Box-Behnken design (BBD) for optimizing fermentation medium conditions. Prodigiosin exhibits strong antimicrobial activity, effectively inhibiting bacteria and fungi, making it a viable eco-friendly alternative to synthetic dyes in the textile industry. Notably, prodigiosin-dyed fabrics can inhibit harmful bacteria like Staphylococcus aureus, suggesting potential uses in hospital textiles and skin health applications. Further research on allergenicity and toxicity is needed to ensure safety